GIAT CERDIK KENDALIKAN HIPERTENSI DI DESA UITIUH TUAN, KECAMATAN SEMAU SELATAN KABUPATEN KUPANG - Awaliyah Muslimah Suwetty; Meldi Emry Lede2; Joli Riyana Nubatonis; Kadek Dedi Setiawan; Orsansi Sunbanu; Iren Biaf (P3M Universitas Aisyiyah Surakarta, 2021)
Hypertension has become one of the causes of high mortality and morbidity and can lead to complications such as heart disease, stroke, and kidney failure. The increase of hypertension in Indonesia included the Uitiuh Tuan village, one of the villages in Kupang district in NTT was very worried. Referred to the Government's program, this CERDIK activity was deemed necessary in order to prevent hypertension from complications. This activity was carried out on January 11, 2020, with the aim of implementing community-based government programs as an effort to detect and prevent hypertension. Implementation activities were divided into three stages, namely preparation, implementation, and evaluation. Activities carried out included services to measured blood pressure, cholesterol checked exercise hypertension, and health education with a total of 103 participants. The results showed that 50% of respondents who has hypertension with a range of values <140/90 mmHg. 56% of respondents have experienced increased cholesterol with a range of values <240 gr/dl and increased knowledge of 20.4%. This discussion has shown that hypertension is caused by negative behavioral triggers, such as consuming unhealthy foods and smoking and alcohol behavior. The recommendations in this activity were to emphasize the existence of community compliance to carried out routine blood checks, light exercise in the morning, and the need to increased knowledge as a CERDIK counter measured in order to reduce the growth rate of hypertension cases in the community.